Evaluasi Fungsi Halte sebagai Tempat Henti Angkutan Umum Studi Kasus Rute Terboyo-Pudakpayung, Semarang - Basuki, Kami Hari (Department of Civil Engineering, Diponegoro University, 2006)
The aim of this study is Bus-stop evaluation at Terboyo - Pudakpayung Corridor for Public Transport line in Semarang City, Indonesia. Evaluation in this study includes bus-stop conditions, convenient level and bus-stop placement. Methodology in this study was improved on two approaches that activity system approach and government policy approach. Point of view in the study was based on user and operator opinions. Bus-Stop condition was observed and analyzed comparing with regulation products.Â According to the analysis, the study was found any bus-stop in low level of services. It can explain because there are long distance between bus-stop, bad condition and dysfunctions. 31% User unused to bus-stop because it far from their home-based activity. Inconvenient bus-stop is shown 9% user opinions. The other hand, more then 51% bus operator pick up passengers from road side. It causing any friction in corridor and make traffic jam. Conclusion in this study is bus-stop at Terboyo-Pudakpayung Corridor in low level of service. There are any suggestions to solve the problem. Long distance between bus-stop is make inaccessible bus-stop, so it certain to build more bus-stop in Terboyo-Pudakpayung corridor. Public Transport information system is needed to improve public transport usage.Keywords: public transport, bus-stop, passengers, operatorPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3954[How to cite: Basuki, K.H., 2006, Evaluasi Fungsi Halte sebagai Tempat Henti Angkutan Umum Studi Kasus Rute Terboyo-Pudakpayung, Semarang, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 3, pp. 287-296]